Pengembangan Bahan Ajar Berbasis Video Animasi Dengan Pendekatan Kontekstual Pada Materi Aritmatika Sosial Kelas VII SMP - Rusli; Said Fachry Assagaf; Selviana (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2023)
The purpose of this research is to develop and produce animated video-based teaching materials with a valid contextual approach. This research is a development research using a 4D model which consists of 4 stages, namely define, design, develop, and disseminate. This animated video teaching material was developed using the powtoon application. The subjects of this research were students of class VII 2 and class VIII 1. The data collected to answer the problem statement in the form of student responses and teacher responses. The research instrument used was a media expert and material expert validation questionnaire, a student response questionnaires and teachers response interview guide. The animation video products produced are 6 videos. The results showed that the animated video-based teaching materials were valid.